1999
DOI: 10.1074/jbc.274.21.15115
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Transactivation Domain of Pax6 by Extracellular Signal-regulated Kinase and p38 Mitogen-activated Protein Kinase

Abstract: The transcription factor Pax6 is required for normal development of the central nervous system, the eyes, nose, and pancreas. Here we show that the transactivation domain (TAD) of zebrafish Pax6 is phosphorylated in vitro by the mitogen-activated protein kinases (MAPKs) extracellular-signal regulated kinase (ERK) and p38 kinase but not by Jun N-terminal kinase (JNK). Three of four putative proline-dependent kinase phosphorylation sites are phosphorylated in vitro. Pax6 is a member of the paired box-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 73 publications
1
80
1
Order By: Relevance
“…p38 phosphorylate PAX6 at the same sites: serines 376 and 413 and threonine 323 (30). This phosphorylation enhances the transcriptional activities of PAX family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…p38 phosphorylate PAX6 at the same sites: serines 376 and 413 and threonine 323 (30). This phosphorylation enhances the transcriptional activities of PAX family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…S1A). This domain mediates activation of Pax-6 through phosphorylation by p38 MAP kinase and homeodomaininteracting protein kinase 2 (15,16). Several phosphorylation sites have been identified in the PST domain of human and zebrafish Pax-6.…”
mentioning
confidence: 99%
“…These features suggest that Pax-6, as a transcription factor, could be modulated by post-translational modifications, such as phosphorylation and dephosphorylation. Indeed, it has been shown that the function of Pax-6 can be modulated by several kinases, including p38, ERK (34), and homeodomain-interacting protein kinase 2 (35). In the present study, we have demonstrated that although both PP-1 and PP-2A are able to dephosphorylate Pax-6 in the in vitro dephosphorylation assays, in the immunoprecipitation-linked Western blot analysis, PP-2A and Pax-6 failed to form interactive complex, and thus, it is unlikely that PP-2A dephosphorylates Pax-6 in vivo.…”
Section: Pp-1 Is a Major Phosphatase That Dephosphorylates Pax-6 In Hmentioning
confidence: 99%
“…1B). It has been shown that phosphorylation of these sites in Pax-6 is carried out by p38, ERK (34), and homeodomain-interacting protein kinase 2 (35). On the other hand, dephosphorylation of Pax-6 remains largely unknown.…”
mentioning
confidence: 99%